2016
DOI: 10.22421/1517-7130.2015v16n4p20
|View full text |Cite
|
Sign up to set email alerts
|

Caracterização dos maus-tratos contra a criança: avaliação das notificações compulsórias na Paraíba

Abstract: Muitas crianças são vítimas de violência, sendo essa uma realidade dolorosa responsável por altas taxas de morbimortalidade. Os profissionais da saúde são obrigados a notificar os maus-tratos cometidos contra crianças e adolescentes. Este estudo objetivou caracterizar os maus-tratos contra a criança, a partir da avaliação das notificações compulsórias na Paraíba. Trata-se de um estudo documental do tipo exploratório descritivo, com abordagem quantitativa. Os dados foram obtidos no Sistema de Informação de Agra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
2
1
4

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 0 publications
0
2
1
4
Order By: Relevance
“…The frequency of reported cases of physical violence in this study was lower than that found in the city of Rio das Ostras, state of Rio de Janeiro, Brazil 15 and higher than that found in the state of Paraíba from 2010 to 2013 16 and in the city of Porto Alegre, state of Rio Grande do Sul. 17 Data from the VIVA Survey from 2011 show that physical assaults were the main type of violence attended by the emergency services, precisely because they are those that leave visible marks on the victims.…”
Section: Discussioncontrasting
confidence: 78%
“…The frequency of reported cases of physical violence in this study was lower than that found in the city of Rio das Ostras, state of Rio de Janeiro, Brazil 15 and higher than that found in the state of Paraíba from 2010 to 2013 16 and in the city of Porto Alegre, state of Rio Grande do Sul. 17 Data from the VIVA Survey from 2011 show that physical assaults were the main type of violence attended by the emergency services, precisely because they are those that leave visible marks on the victims.…”
Section: Discussioncontrasting
confidence: 78%
“…Most reports of neglect came from the state of Paraíba between 2010 and 2013, reaching an 81% frequency. 28 In the municipalities of Porto Alegre, state of Rio Grande do Sul, 29 and in Rio das Ostras, Rio de Janeiro, 30 neglect reached frequencies of 41% and 36.8%, respectively, with magnitudes only lower than those of sexual violence. These frequencies were closer to that found for the state of Espírito Santo.…”
Section: Discussionmentioning
confidence: 98%
“…17,26 Diferentes autores destacam que as violências contra a infância no espaço privado da residência contribuem para a subnotificação dos casos, favorecendo a proteção aos agressores e o silêncio das vítimas. 19,27,28 A residência também é identificada como o principal ambiente da violência contra a criança, seja nas contribuições da literatura, seja no Sinan, cujos dados mostram uma frequência da violência no espaço reservado à família variar de 49,6%, em uma regional de saúde de Minas Gerais, a 77,0% no território do estado da Paraíba. 17,27 Este estudo encontrou que os pais são os principais perpetradores da violência recorrente.…”
Section: Discussionunclassified
“…19,27,28 A residência também é identificada como o principal ambiente da violência contra a criança, seja nas contribuições da literatura, seja no Sinan, cujos dados mostram uma frequência da violência no espaço reservado à família variar de 49,6%, em uma regional de saúde de Minas Gerais, a 77,0% no território do estado da Paraíba. 17,27 Este estudo encontrou que os pais são os principais perpetradores da violência recorrente. Este achado, comum a outros trabalhos, 12,16,18,23 demonstra a realidade da criança a conviver diariamente com seu(s) agressor(es), justamente a quem cabe o papel fundamental de protegê-la e educá-la.…”
Section: Discussionunclassified
See 1 more Smart Citation